Murder they cried: Revisiting medicine murders in literature - Maake, Nhlanhla (My University, 1996)
In July 1949 the British Government appointed an anthropologist from Cambridge. G. I. Jones, to inquire into the diretlo murders in the Protectorate of Basutofand. From the report which he compiled, the occurrence of the murders is recorded from 1895, where there were 6 reported cases in that year, rising and declining through the years, until they reached a peak of 20 in 1948 (Jones, 1951:104). According to Jones' report, among a variety of reasons which were responsible for the epidemic political and administrative changes which involved positions of marena (chiefs) and boramotse (headmen) seem to be the uppermost for the practice of diretlo murders. Medicine murder, a concept which is often translated as ritual murder, in Sesotho is dircilo, a cognate of ditlo: According to Jones' definition: "Ditto is the traditional name for flesh and other parts of the body obtained from the body of an enemy killed in the normal course of warfare... diretlo is not obtained from bodies of strangers or enemies, but from a definite person who is thought to possess specific attributes considered essential for the particular medicine being made." We are further informed that a person marked for diretlo is "usually a member of the same community and is frequently a relative of some of the killers. He is killed specifically for this diretlo which has to be cut from his body while he is alive" (1951:14). These diretlo were mixed as an ingredient for a lenaka (horn) medicine. My interest in this phenomenon is limited to the period 1910 and 1960. These dates have no historical significance, but mark the time of the writing or publication of the Sesotho literary texts which deal mainly with diretto murders as a theme. Those which I would like to study in this discussion are: Mofolo's Chaka (1925), Matlosa's Katiba (1950), Mopeli-Paulus' Liretlo (1950) and Khaketla's Mosali a Nkhola (1960). I will also refer to Guma's Morena Mohlomi, Mor'a Monyane (1960), and Ntsane's Nna Stijene Kokobela CID (1963). In critical writings on the literature of Basutoiand so far diretlo has never been addressed as a major theme in these works. Studies generally tend to see this theme as part of the run of the mill Christianity versus Sesotho traditions. This discussion is meant to redress this shortcoming. It also sets out, with reference to the abovementioned texts, to look at the nature of intertextuality - the coreference of texts, and also to study how far given writers could be said to reflect the fears and aspirations of their society, more from an applied than a theoretical perspective. The concept of intertextuality will be broadened so that the social and historical discourse which forms the context of the text will be regarded as text. Bearing the above definition of diretlo in mind, I would like to consider the literary texts in the chronological order of their publication, starting with Mofolo's Chaka. The year 1910 is noted as the time when Mofolo completed the manuscript of this novel.
African Studies Seminar series. Paper presented 5 August 1996
Keywords: Murder in literature; Southern African fiction. Criticism and interpretation